Determinants of Outpatient Satisfaction in Regional Public Hospitals: The Dominant Role of Waiting Time and Process Quality in Indonesia - Norsaputera, Eka; Hamzah, Hamzah; Harun, Lukman (Majalah Kesehatan Indonesia, 2025)
This study examined factors associated with outpatient patient satisfaction at Datu Sanggul Regional Public Hospital, Rantau, integrating Donabedian’s structure–process–outcome, SERVQUAL, and Swanson’s Caring Theory to explicitly link facilities (structure) and waiting time, social interaction, service effectiveness, and nurse caring (processes) to satisfaction (outcome). Using purposive sampling justified by operational access to experienced OPD users, we surveyed N = 124 adults in June 2025 with 5-point Likert instruments adapted via forward–back translation, expert review, and pilot testing. Descriptive statistics summarized domains; bivariate associations used chi-square (α = .05). Multivariable analysis applied ordinal logistic regression with assumption checks (multicollinearity, logit linearity where applicable, Test of Parallel Lines), and sensitivity plans for partial proportional odds when required. The final model outperformed the intercept-only model (likelihood ratio p < .001) and explained substantial variation (Nagelkerke R² = 0.66). Waiting time showed a strong negative association with satisfaction (Estimate = −6.710, p = .001), while social interaction, service effectiveness, and nurse caring were not statistically significant after adjustment. Findings emphasize process improvements—particularly queue transparency and throughput optimization—over incremental facility enhancements once adequacy thresholds are met. The study advances evidence from regional Indonesian hospitals, offering actionable levers for patient-centered outpatient redesign.